DISCOURSE ON THE IMPLEMENTATION OF PROGRESSIVE LAW IN RECOVERING STATE LOSSES DUE TO CRIMINAL ACTS OF CORRUPTION - Yopi Gunawan (Jurnal Pembaharuan Hukum, 2021)
The number of corruption cases in Indonesia that are not appropriately resolved is the cause of the emergence of progressive laws. Public trust in the law began to fade because the applicable law did not determine many problems. The law is not seen as a solution provider, and it becomes a particular problem for law enforcement. This article aims to analyze the concept of recovering state losses due to corruption through the implementation of progressive law. The method used is normative legal research using a qualitative approach. This article concludes that progressive law enforcement to eradicate criminal acts of corruption lies in harmonizing the values contained in society and then realizing those values into reality, where their application is influenced by several factors, including legal substance, legal structure, culture law, professionalism, and leadership. The development of the modus operandi of corruption in hiding assets resulting from corruption encourages the urgency of implementing a progressive law enforcement strategy by implementing 2 (two) strategic steps, namely: a) Taking rule-breaking actions in the form of seizure of the defendant's assets to guarantee payment of state losses; b) The judge gives a contra legem decision in the form of an obligation to pay replacement money without a subsidiary which is preceded by confiscation of the guarantee so that it will close the defendant's room to escape from paying replacement money